Catechetical Discourse a Handbook for Catechists - St. Gregory of Nyssa (3GdbOjS ZQjZhQjhS GdfjSjs approximately 335-394; Ignatius Green (New York, USA St. Vladimir's Seminary Press, 2019)
"St Gregory of Nyssa (c. 335-c. 394) wrote the Catechetical Discourse (Oratio catechetica) for his catechists, who instructed those preparing for baptism. In the work, he expounds the fundamental doctrines of the Christian faith: the Trinity, creation, the image of God in man, the fall, the nature of evil, Christ's birth, death, harrowing of hades, and resurrection, and the sacraments of baptism and the Eucharist. He provides his catechists with strategies to defend the faith against objections and to articulate doctrine in a winsome way. He used his rhetorical training to do this, crafting the Catechetical Discourse on the model of an "On Invention" rhetorical handbook"--
Keywords: Patristics (3Yde GdBHGFjGJs; Theology, Doctrinal -- Early church, ca. 30-600; Patrology; History